The Success of Problem-Based Learning (PBL) Method on the Improvement of TOEFL Preparation Listening Score at UPT Bahasa Universitas Khairun Students Course - Fitriningsih Pratiwi Mahmud (English Education Department, Faculty of Education Muhammadiyah University of North Maluku, 2023)
This research aims to examine the success of Problem-Based Learning (PBL) on the improvement of TOEFL preparation listening score at UPT Bahasa Universitas Khairun students course. This research performed an experimental study with paired-sample t-test. The subjects in this study were 20 students. The sampling is through the cluster sampling method, in which samples taken are classes. The classes that are used as sample selection will later become the experimental group classes for the study purposes. This study uses two types of instruments, which are; pretest to measure participants' initial scores from the TOEFL listening preparation program and the posttest to measure the final scores of participants related to the success of applying PBL method. The data then analysed quantitatively by using the paired-sample t-test in SPSS IBM 25. The results show that the minimum score is increased by 1 point from Min1=31 to Min2=32. While the maximum score is increased by 4 points from Max1=61, to Max2=65. The findings attest that the PBL method applied on TOEFL listening preparation course conducted in Unkhair has been successfully improved students’ listening score.